Programa De Estimulación En Funciones Ejecutivas Y Habilidades Emocionales A Estudiantes Grado 11, De La Institución Educativa Caracolí (2023)
The low development in executive functions significantly alters the central nervous system, so it is of vital importance its potentiation. Likewise, it is evident that emotional skills strengthen executive functions and also help the development of personality and improve emotional intelligence.